The Cost of Creativity in the Work of Gabriel Josipovici - Victoria Best (Revue LISA)
This article explores Gabriel Josipovici’s preoccupation with the human cost of creating art in his theoretical, autobiographical and fictional works. It considers in particular the relationship between creativity and family bonds with special reference to the unusually deep bond that formed between the author and his mother.